2021
DOI: 10.1097/rli.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ascending Aortic Flow in Patients With Degenerative Aneurysms

Abstract: Objectives: Degenerative thoracic aortic aneurysm (TAA) patients are known to be at risk of life-threatening acute aortic events. Guidelines recommend preemptive surgery at diameters of greater than 55 mm, although many patients with small aneurysms show only mild growth rates and more than half of complications occur in aneurysms below this threshold. Thus, assessment of hemodynamics using 4-dimensional flow magnetic resonance has been of interest to obtain more insights in aneurysm development. Nonetheless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Evidence exist, that ultrasonographic elastography methods provide additional information on pure morphological information that can be helpful after endovascular repair of aortic aneurysms or in multiparametric vascular ultrasound imaging 22 , 23 . Furthermore, in the last years, 4D-flow and MR elastography have been used to investigate the complex interaction of aortic wall and diameter changes in patients with aneurysm 24 26 . In a recent study, Dong et al found lower abdominal aortic stiffness and stiffness ratio measured by MR elastography to be associated with aneurysmal events 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exist, that ultrasonographic elastography methods provide additional information on pure morphological information that can be helpful after endovascular repair of aortic aneurysms or in multiparametric vascular ultrasound imaging 22 , 23 . Furthermore, in the last years, 4D-flow and MR elastography have been used to investigate the complex interaction of aortic wall and diameter changes in patients with aneurysm 24 26 . In a recent study, Dong et al found lower abdominal aortic stiffness and stiffness ratio measured by MR elastography to be associated with aneurysmal events 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Flow velocities, flow volumes, and wall shear stress could provide additional and potentially complementary information for clinical guidance and therapy. Four-dimensional PC flow offers a comprehensive overview and potentially new insights into the pathophysiology of different disease entities (eg, aortic aneurysms, 83 mitral and aortic valve pathology, 84,85 intracardiac pathology 86 ) and might ultimately help to predict disease outcome and patient prognosis 87,88 . Detailed protocol recommendations for cardiac 89 and aortic 90 4D flow can be found elsewhere.…”
Section: Phase-contrast Flow Imagingmentioning
confidence: 99%
“…Numerous studies have shown that in AAA, rupture sites occur in areas of low WSS and in most cases are close to areas of flow stagnation with higher intraluminal thrombus deposition [ 5 – 8 ]. In addition, WSS is also used to assess hemodynamics in the patients with thoracic aortic aneurysm and aortic dissection [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%